Nanocellulose from a colloidal material perspective - Sanchez-Salvador, Jose Luis; Xu, Hongyu; Balea, Ana; Negro, Carlos; Blanco, Angeles (Frontiers in Materials, 2023)
Cellulose nanomaterials present unique properties of interest for their many applications. Their behavior is mainly related to the colloidal properties that determine their self-assembly and stability mechanisms as well as their interaction with the particles present in different matrices. This review shows the state of the art of nanocellulose from a colloidal material perspective, from the approach of how to control these properties and their influence on the final products, such as drug delivery, coatings, nanocomposites, or tissue engineering, emphasizing the role of colloidal behavior in determining their performance.